Anatomy of the larynx and pharynx: effects of age, gender and height revealed by multidetector computed tomography. (18th April 2015) - Inamoto, Y.; Saitoh, E.; Okada, S.; Kagaya, H.; Shibata, S.; Baba, M.; Onogi, K.; Hashimoto, S.; Katada, K.; Wattanapan, P.; Palmer, J. B.
Summary Although oropharyngeal and laryngeal structures are essential for swallowing, the three‐dimensional (3D) anatomy is not well understood, due in part to limitations of available measuring techniques. This study uses 3D images acquired by 320‐row area detector computed tomography ('320‐ADCT'), to measure the pharynx and larynx and to investigate the effects of age, gender and height. Fifty‐four healthy volunteers (30 male, 24 female, 23–77 years) underwent one single‐phase volume scan (0·35 s) with 320‐ADCT during resting tidal breathing. Six measurements of the pharynx and two of larynx were performed. Bivariate statistical methods were used to analyse the effects of gender, age and height on these measurements. Length and volume were significantly larger for men than for women for every measurement (P < 0·05) and increased with height (P < 0·05). Multiple regression analysis was performed to understand the interactions of gender, height and age. Gender, height and age each had significant effects on certain values. The volume of the larynx and hypopharynx was significantly affected by height and age. The length of pharynx was associated with gender and age. Length of the vocal folds and distance from the valleculae to the vocal folds were significantly affected by gender (P < 0·05). These results suggest that age, gender and height have independent and interacting effects on the morphology of the pharynx and larynx. Three‐dimensional imaging and morphometrics using 320‐ADCT are powerful tools for efficiently and reliably observing and measuring the pharynx and larynx.